(untitled) (Altre Modernità, 2014)
This paper proposes a literary reading centered on the absence of the father as a narrative and psychological element of Sandra Lorenzano’s novel, Fuga en mí menor. The search for the father as a necessary process to configure one’s identity becomes an interior escape, leading the main character to work out a suspended mourning, which finds expression in art and music. The metaphoric pun in the title itself announces the meaning of the escape as a double movement, musical and interior, and anticipates the structure that revolves around one single theme whose counterpoints are the different voices and linguistic codes used by the author, which put music and photography in the focus. The threads of heteroglossia weave individual and collective memory; the sounds and silences, the lights and shadows, European history during the Second World War and Argentine history during the dictatorship as moments that have forced people into exile. In the novel the classic paradigm of Telemachus takes on the shape of exile with all its meaning of separation and loss, and leads to the discovery of being an orphan as a necessary condition to inherit from the father, that is, inherit the possibility of opening up new meanings to the world, as the only possible way to give meaning to the experience of life, to your own history.